Manajemen Peserta Didik Berbasis Karakter dalam Membentuk Generasi Berintegritas di SMA Al-Islam Krian - Wulan, Amalia Wulan Mahardika Putri; Ayasha Nabila Audiya Nency; Indah Putri Purwati; Adtora Aprilianto Bagaskara; Ayu Wulandari (CV Putra Publisher, 2024)
This study aims to develop quality and achievement in educational institutions, such as schools. This study uses a qualitative research approach, namely field research. The data obtained through interviews, observations, and documentation from various sources including teachers and students. The main function of student management is as a means for students to develop their characteristics to the maximum, both in terms of individual, social, aspirations, and their potential. The results of this study indicate that student management plays an important role in integrating that students refer to a group of students who have strong moral values ​​and are able to apply them in their daily lives. They are expected to demonstrate honesty, responsibility, and ethics in various aspects, such as academics, social interactions, and personal decisions. The character of student integrity has been possessed by each individual student but perhaps in the implementation of the implementation it is still not optimal, there are some students who have not implemented a character of integrity properly. This study provides significant insight into the development of educational policies and practices, and provides practical suggestions to improve the effectiveness of its implementation in educational institutions.